Regorafenib in glioblastoma recurrence: A case report. (2021) - Detti, Beatrice; Scoccianti, Silvia; Lucidi, Sara; Maragna, Virginia; Teriaca, Maria Ausilia; Ganovelli, Michele; Desideri, Isacco; Lorenzetti, Victoria; Scoccimarro, Erika; Greto, Daniela; Livi, Lorenzo
Abstract: GBM (glioblastoma multiforme) is the most common and aggressive brain tumor. To date, treatment options for glioblastoma recurrence are lacking. Recently, REGOMA trial showed the superiority of regorafenib to lomustine in patients with first glioblastoma recurrence. We report an excellent response to three months treatment with regorafenib, in a patient who presented a rapid progression after the end of post operative radio-chemotherapy and after only one cycle of adjuvant TMZ (Temozolomide).